Continued Progress Promising Evidence on Personalized Learning - Pane, John F. (RAND Corporation, 2015)
This report examines achievement in 62 schools pursuing a variety of personalized learning practices, and implementation details in 32 of the schools. It uses data from site visits, interviews, and surveys to create a broad picture of efforts to implement personalized learning and the perceptions of teachers and students. Achievement data for personalized learning students are compared to a matched group of students attending other schools.